THE ROLES OF ICT IN CULTIVATING THE CHARACTER OF ELEMENTARY SCHOOL STUDENTS - Octavia Widiastuti; Agus Soleh; Teguh Sulistyo (Institut Teknologi Sepuluh Nopember, 2018)
The use of Information and Communication Technology (ICT) in all levelsof education has been implemented broadly for years. This paper aims atreporting the power of ICT in cultivating elementary school students’character. The recent study, basically, is twofold: First, to find outelementary school students’ perceptions towards the use of ICT in the formof short videos and Hot Potatoes in the classrooms; second, to investigatethe positive character of the students appearing during the implementationof ICT. There were 45 fifth graders of an elementary school joining theproject. They were treated using ICT in the classroom, and they wereencouraged to express their opinion dealing with the use of ICT in theclassroom. The findings of the present study suggest that teachers shouldfacilitate their students with ICT for it is necessary to build positive studentcharacter, and it motivates them to be more curious in the teaching andlearning process.